CoPhiEditor: The DSL-Based DSE Methodology within the ERC Advanced Grant 885222-GreekSchools - Simone Zenzaro; Angelo Mario Del Grosso; Federico Boschetti; Graziano Ranocchia (Umanistica Digitale)
This paper explores the integration of traditional philological methods with computational approaches, aiming to establish a more effective and rigorous framework for textual studies. To this end, we propose a preliminary set of evaluation criteria—familiarity, transparency, completeness, compactness, consistency, and actionability—for analyzing text editing tools. Using this framework, we suggest the use of Domain-Specific Languages (DSLs) for the digital papyrological editions of the ERC-885222 GreekSchools project that is our case study. We introduce CoPhiEditor, a software platform designed to support the creation of Digital Scholarly Editions through the use of DSLs. This approach enables scholars to retain familiar workflows while benefiting from machine-actionable data representations and computational functionalities. Key features of CoPhiEditor include its recursive data model, automatic error-checking and suggestions, automatic TEI-conformant serialization, and advanced collaboration capabilities that streamline teamwork on shared projects. Furthermore, its extensible and domain-agnostic architecture broadens its applicability across various scholarly editing contexts. The aim of CoPhiEditor allows philologists to incorporate digital tools without sacrificing their established editorial practices.